Welfare Reform and Children's Health - Badi H. Baltagi; Yin-Fang Yen (Institute for the Study of Labor (IZA), 2014)
This study investigates the effect of the Temporary Aid to Needy Families (TANF) program on children's health outcomes using data from the Survey of Income and Program Participation (SIPP) over the period 1994 to 2005. The TANF policies have been credited with increased employment for single mothers and a dramatic drop in welfare caseload. Our results show that these policies also had a significant effect on various measures of children's medical utilization among low-income families. These health measures include a rating of the child's health status reported by the parents; the number of times that parents consulted a doctor; and the number of nights that the child stayed in a hospital. We compare the overall changes of health status and medical utilization for children with working and nonworking mothers. We find that the child's health status as reported by the parents is affected by the maternal employment status.
Keywords: I1; I3; 330; maternal employment; children's health; welfare reform; fixed effects